SURVEI SARANA DAN PRASARANA PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA SEKOLAH MENENGAH PERTAMA DI KABUPATEN PRINGSEWU TAHUN 2019 - Nur Afifah Sudibyo; Reza Adhi Nugroho (Universitas Teknokrat Indonesia, 2020)
The purpose of this study is to determine the condition of learning facilities and infrastructure of Physical and Sports Physical Education in junior high schools in Pringsewu, 2019. The method of the research used by the writer is qualitative methods, because it describes the availability of learning facilities and infrastructure of Physical and Sports Physical Education through the number of facilities and infrastructure that is available and is needed in learning. Data collection is done by using documentation, observation, and questionnaires. The research instrument that is provided in the form of a questionnaire is the availability of sports facilities and infrastructure. According to the result of the research conducted in State Junior High School, Pringsewu has been able innovating in creating sport modification tools. The modifications made even more widely used for learning in the athletics branch by utilizing simple materials. Each teacher is guided to provide an innovation and modification of the tools for the achievement of the learning process. Keywords: Facilities, Infrastructure, Learning, Physical education, sports and health, Junior High School